Project-based learning: an environment to prepare IT students for an industry career - Alves, Luís M. (2014)
The lack of preparation of Software Engineering (SE) graduates for a professional career is a common complaint raised by industry practitioners. One approach to solving, or at least mitigating, this problem is the adoption of the Project-Based Learning (PBL) training methodology. Additionally, the involvement of students in real industrial projects, incorporated as a part of the formal curriculum, is a well-accepted means for preparing students for their professional careers. The authors involve students from BSc, MSc, and PhD degrees in Computing in developing a software project required by a real client. This chapter explains the educational approach to training students for industry by involving them with real clients within the development of software projects. The educational approach is mainly based on PBL principles. With the approach, the teaching staff is responsible for creating an environment that enhances communications, teamwork, management, and engineering skills in the students involved.